ELEMENTARY STUDENTS’ POETRY WRITING SKILLS USING PICTURE CARD-ASSISTED ACROSTIC TECHNIQUES - Cahyati, Nuri; Hartati, Tatat (International Conference on Elementary Education, 2025)
Poetry writing skills for fifth grade elementary school students by applying acrostic techniques supported by picture cards as a learning medium. This research aims to improve the poetry writing skills of 5th grade elementary school students by using the acrostic technique supported by picture card learning media. The method used was qualitative with a case study approach, involving 30 students from SDN X. Data was collected through observation, in-depth interviews, and analysis of students' poetry before and after the intervention. Learning is carried out in six sessions, where students learn to compose poetry based on the words on picture cards and the data that will be obtained is the results of students writing poetry using the acrostic technique. Using acrostic techniques and picture cards will make it easier for students to write poetry. In addition, students also show progress in emotional expression in their work. Interviews with students and teachers show that the use of picture cards not only increases students' motivation and self-confidence, but also makes the learning process more enjoyable.